A new weapon: the application of tumor vaccines based on extracellular exosomal heat shock proteins in immunotherapy - Yi, Kexin; Sun, Chengpeng; Yuan, Yalin; Luo, Zhaowei; Luo, Hongliang; Xie, Yunhe (Frontiers in Immunology, 2025)
Despite the significant advancements in cancer research, innovative approaches are still needed to reduce tumor incidence, progression, and dissemination, as well as for prolonging patient survival. Currently, the development of cancer vaccines is gaining attention as a novel preventative and therapeutic strategy. Although the concept of cancer vaccination is not new, a limited number of vaccines have received approval for tumor therapy. Heat shock protein (HSP)-based vaccination represents a promising strategy that harnesses specific tumor antigens to activate immune responses. Exosomes (Exs) are highly heterogeneous bilayer vesicles capable of transporting various types of molecules through extracellular space. Compared with conventional anticancer drugs, exosomes exhibit low toxicity and good biocompatibility, and they can stimulate the immune system either directly or indirectly. Ex-based vaccines may elicit an antitumor immune response that generates memory cells capable of recognizing cancer antigens, thereby inhibiting disease progression. This paper reviews the potential applications of HSPs and exosomes in the prevention and treatment of solid tumors. Finally, we discuss the advantages of the extracellular exosomal heat shock protein (HSP-Ex1) vaccine and future research directions aimed at optimizing heat shock protein-based cancer immunotherapy strategies.